Preparing Nanofluids (Al2O3) for Enhancement Performance of Photovoltaic - Mohammed Saadoon; Ibtisam Hasan; Mohammed Mohammed (Engineering and Technology Journal, 2021)
Photovoltaic (PV) panels produce electrical energy comparable to the cumulative amount of PV radiation generated on surface of sun. The solar modules influence on temperature of PV panel and for work with its standard specifications in Iraqi environment can be used nanofluid for cooling PV and improve performance. The developed thermal model for proposed cooling method has shown on the way to be an efficient design tool that can help engineers to reduce the time and cost of experimental testing. The improvement in temperature reduction using direct flow technique at rear sides of PV panel achieved electrical and thermal performance enhancement. The enhancement of overall efficiency at 1 g of nanofluid  is  showed  15%  but in 1.5g  nanofluid is  18%. As well as the enhancement of thermal efficiency at 1 g and1.5g of nanofluid are showed 19% and 27% respectively. So in Electrical efficiency at 1 g of nanofluid is showed 11% and in 1.5g  nanofluid is  14%.The experimental results have shown that the utilization of nanofluid (Al2O3) as a result of its high thermal conductivity and tiny particle size. The coefficient of heat transfer and Nusselt number increasing with the increase of concentration of nanofluid, It can be concluded that has great impact, especially in Iraq condition where the temperature is normally high and can improve their performance and efficiency by adding nanofluid for cooling system.